2013
DOI: 10.1149/2.074306jes
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrochemical Activity of Pt Supported on Three-Dimensional WO3·0.33H2O Networks for Methanol and Ethanol Oxidation

Abstract: Tungsten oxide (WO3·0.33H2O) networks and nanorods were prepared by a hydrothermal method. Platinum nanoparticles were distributed on the two types of WO3·0.33H2O nanostructures for the methanol and ethanol electrooxidation. The synthesized WO3·0.33H2O nanostructures and WO3·0.33H2O supported platinum (Pt/WO3·0.33H2O) catalysts are characterized by X-ray diffraction, scanning electron microscope and high resolution transmission electron microscope. The electrocatalytic properties of the Pt/WO3·0.33H2O composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Direct methanol fuel cells (DMFCs) have attracted much attention as power sources for portable devices and fuel-cell vehicles due to their good power efficiency, low operation temperature, and easy transportation and storage of methanol compared with H 2 gas fuel cells. 1 Pt-based catalysts supported on carbons play a signicantly important role in catalyzing methanol oxidation reaction (MOR). 2 However, there are still a lot of challenges facing the wide commercialization of the applications of Pt-based catalysts, such as high cost, low catalytic efficiency and poisoning effect.…”
Section: Introductionmentioning
confidence: 99%
“…Direct methanol fuel cells (DMFCs) have attracted much attention as power sources for portable devices and fuel-cell vehicles due to their good power efficiency, low operation temperature, and easy transportation and storage of methanol compared with H 2 gas fuel cells. 1 Pt-based catalysts supported on carbons play a signicantly important role in catalyzing methanol oxidation reaction (MOR). 2 However, there are still a lot of challenges facing the wide commercialization of the applications of Pt-based catalysts, such as high cost, low catalytic efficiency and poisoning effect.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Nanostructured electrodes can be made with tethered nanomaterials, 11 threedimensional composites 12 and templating methods. 13 Three-dimensional nanostructured electrode systems are of particular interest because of the central role diffusion and surface area plays in electrochemical processes.…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructured metal electrodes are widely applied as electrochemical sensors because they possess advantages over bulk materials, including enhanced mass transport, higher active surface area, and enhanced surface and electronic properties. Nanostructured electrodes can be made with tethered nanomaterials, three-dimensional composites, and templating methods . Three-dimensional nanostructured electrode systems are of particular interest because of the central role diffusion and surface area play in electrochemical processes. These types of structures have been shown to present highly effective solutions for the development of new battery materials, sensors, hydrogen fuel cells, and photoelectrochemical devices .…”
Section: Introductionmentioning
confidence: 99%
“…Methanol is usually utilized as fuel because it can be more efficiently oxidized than other small organic molecules, and ethanol is one of the most promising fuels with its low toxicity, abundance, low permeability across proton exchange membrane and high energy density. [1][2][3] Until now, though it has been found that a few metallic oxides have catalytic activity for alcohol electrooxidation, Pt-based electrocatalysts have been considered the most promising electrode materials for electrooxidation of methanol or ethanol due to the good electrochemical stability and favorable electrocatalytic activity. [4][5][6] The electrocatalysts are mainly consisted of Pt nanoparticles and a certain support material.…”
mentioning
confidence: 99%